2018
DOI: 10.1088/1741-2552/aac960
|View full text |Cite
|
Sign up to set email alerts
|

Integrating artificial intelligence with real-time intracranial EEG monitoring to automate interictal identification of seizure onset zones in focal epilepsy

Abstract: The successful validation of our approach on a large cohort of 82 patients warrants future investigation on the feasibility of utilizing intra-operative EEG monitoring and artificial intelligence to localize epileptogenic brain tissue. Broadly, our study demonstrates the use of artificial intelligence coupled with careful feature engineering in augmenting clinical decision making.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 87 publications
6
67
0
Order By: Relevance
“…15,16 This promoted the development of combinations of several markers for achieving a better identification of the EZ. 17, 18 Cimbalnik et al proposed that a multifeature approach based on HFO rates, univariate and bivariate connectivity measures is superior to single marker approaches; surgical outcome was correctly predicted in 89% of patients when applying this approach to a 30-minute section of intracranial electroencephalography (iEEG). 19 Variations across the sleep-wake cycle are not negligible, when assessing markers of the EZ, 20-22 a fact often not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This promoted the development of combinations of several markers for achieving a better identification of the EZ. 17, 18 Cimbalnik et al proposed that a multifeature approach based on HFO rates, univariate and bivariate connectivity measures is superior to single marker approaches; surgical outcome was correctly predicted in 89% of patients when applying this approach to a 30-minute section of intracranial electroencephalography (iEEG). 19 Variations across the sleep-wake cycle are not negligible, when assessing markers of the EZ, 20-22 a fact often not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the concept of the "EZ" has been used for more than 50 years (Bancaud et al, 1965), its precise definition remains controversial, and a reliable biomarker is still missing. Several algorithms have been proposed to assess the extent of the EZ and compare it with either the EZ area identified by an expert clinician or the resected region (Andrzejak et al, 2014;Bartolomei et al, 2008;David et al, 2011;Gnatkovsky et al, 2011Gnatkovsky et al, , 2014Varatharajah et al, 2018).…”
Section: Validation Of An Ez Biomarkermentioning
confidence: 99%
“…Phase-amplitude coupling (PAC) is a form of cross-frequency coupling 43 where the amplitude of a higher frequency oscillation is modulated by the phase of a lower frequency oscillations. Recent studies [32][33][34][35] have shown that high PAC values are related with the SOZ. There are many proposed methods to estimate PAC [44][45][46][47][48][49][50] and different parameter choices that can be made (i.e.…”
Section: Phase Amplitude Couplingmentioning
confidence: 99%
“…There is no systematic study evaluating the performances of PAC in localizing the epileptogenic tissue using either different PAC implementations or the different parameters choices. We decided to investigate our dataset computing PAC between the modulating phase of theta band activity (4-8 Hz) and the amplitude of gamma activity (30-80 Hz) because this frequency band pairs were successfully investigated in recent epilepsy related studies [32][33][34][35] . For the detailed formula see Appendix .…”
Section: Phase Amplitude Couplingmentioning
confidence: 99%
See 1 more Smart Citation